Structured Parenting and Child Independence in Autism: A Socioeconomic Comparison - Irawati, Sutiyah Nova; Supriyono, Supriyono; Redjeki, Endang Sri; Zulkarnain, Zulkarnain (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2026)
The presence of a neurodevelopmental disorder characterized by persistent social-communicative impairments and restricted behavioural patterns significantly disrupts family organizational structures and established daily routines. Families navigating the care of a child with such a diagnosis encounter multifaceted challenges, including considerable time commitments necessitated by engagement in intensive therapeutic modalities and substantial financial burdens. Furthermore, caregivers must maintain considerable scheduling adaptability to address the individualized behavioural profiles and developmental requirements of their diagnosed offspring. This investigation employed a qualitative phenomenological methodology encompassing structured observation protocols, semi-structured interviewing procedures, and documentary analysis. The final sample encompassed 12 dyadic parent-child units from heterogeneous socioeconomic backgrounds, spanning upper to middle-class socioeconomic classifications. The findings reveal that upper-middle-class families tend to implement structured and consistent parenting strategies, including the use of visual schedules, family-based monitoring systems, and regular progress evaluations, which support the development of children’s independence. In contrast, lower-middle-class families often rely on adaptive and improvised strategies due to financial constraints and work-related fatigue, resulting in less consistent intervention practices. The study also found that while higher socioeconomic status is associated with more structured parenting approaches, it is also linked to higher levels of parental stress due to increased expectations and involvement in intensive interventions.